Estimation and cancellation of transponder distortions in satellite forward links using memory polynomials. (16th April 2018) - Dimitrov, Svilen
Summary: In this paper, a practical non‐linear equalizer with iterative distortion cancellation in a satellite receiver is studied. Assuming no prior satellite channel knowledge, distortion estimation and cancellation are performed at the receiver by means of a memory polynomial model used for channel estimation. A data packet transmission scenario over a single‐carrier satellite transponder is simulated, using the not‐linearized amplifier and onboard filter characteristics similar to the direct‐to‐home broadcast DVB‐S2X reference scenario. Varying the memory depth and the non‐linear order of the memory polynomial model trained in the receiver, we compared the packet‐error rate performance of the practical non‐linear equalizer to the standard fractionally spaced linear adaptive equalizer, as well as to an implementation of the non‐linear equalizer with ideal channel knowledge at the receiver. The improved receiver demonstrates superior performance as compared with the standard linear equalizer with up to 5.48‐dB energy efficiency gain for 64‐amplitude and phase‐shift keying for a practical memory polynomial set‐up, and it approaches consistently the packet‐error rate performance of the implementation with ideal channel knowledge when increasing the memory depth and the non‐linear order. Furthermore, it enables the use of high‐order modulation up to 256‐amplitude and phase‐shift keying in the studied scenario, improving significantly the spectral efficiency of the air interface. Abstract : A practical non‐linear equalizer is proposed for application in a DVB‐S2X satellite receiver. Assuming no prior satellite channel knowledge, iterative distortion estimation and cancellation are performed using a memory polynomial model for channel estimation. Varying the memory depth and the non‐linear order, the practical non‐linear equalizer approaches the packet‐error rate performance of the implementation with ideal channel knowledge. It outperforms the standard fractionally‐spaced linear equalizer in a single‐carrier direct‐to‐home broadcast DVB‐S2X reference scenario, and enables high‐order modulation up to 256‐APSK.